Application of Sociodrama Techniques Based on Tabe Culture to Improve Polite Character - Sukiman, Nurfajriyanti; Latif, Suciani; Zulfikri, Zulfikri (Konseling Edukasi : Journal of Guidance and Counseling, 2026)
Application of Sociodrama Techniques Based on Tabe Culture to Improve Polite Character. This study aims to describe the character of students' politeness, the implementation of group guidance services with sociodrama techniques based on tabe culture , and the effect of its application on improving politeness. Tabe culture is a form of politeness typical of the Bugis-Makassar community which is manifested through the expression "tabe" and hand gestures as a sign of respect, permission, and appreciation, which contains the values of sipakatau, sipakalebbi , and sipakainge . The study used a quantitative approach with a quasi-experimental design of the non-equivalent control group pretest–posttest type . The sample consisted of 18 students selected through purposive sampling , 9 students each in the experimental and control groups. Data were obtained through questionnaires and observations, then analyzed using descriptive statistics and independent sample t-test . The results showed that before the treatment, students were in the medium and low categories, characterized by behaviors such as mocking, indifference, and lack of respect for teachers and friends. The t-test showed a significance of 0.001 (<0.05), so that sociodrama based on tabe culture had a significant effect in improving students' respectful attitudes, polite language, and social behavior.Keywords: Character of good manners; Sociodrama Technique; Tabe Culture ; Group Guidance.